Mathematical model of multifractal dynamics and global warming - Kudinov, Alexei Nikiforovich; Krylova, Olga Igorevna; Tsvetkov, Victor Pavlovich; Tsvetkov, Ilya Viktorovich (Eurasian Mathematical Journal, 2014)
In this work the variations of global temperature that have occurred in the period from 1860 up to now are analyzed on the basis of the concept of multifractal dynamics. The multifractal curve describing dynamics of global temperature for this period of time has the following values of fractal dimensions over 5 periods lasting for 30–31 years each, accordingly: \( D_1 = 1.140 \), \( D_2 = 1.166 \), \( D_3 = 1.141 \), \( D_4 = 1.203 \), \( D_5 = 1.183 \). Such relatively small values of fractal dimensions are indicative of essentially determined character of processes responsible for variations of global temperature. Our predictive estimates provide 0.5\(^°\)C increase in global temperature by 2072, thereby confirming maintenance of the tendency of global warming in the near future.